Uso do balé clássico no ensino de física: uma sequência didática para o estudo de rotação - Silva, Giovana Maria da (My University, 2026)
The work presented relates physics to the study of a classic ballet movement called pirouette. Students in high school have little contact with arts, and the idea was to approximate them and create some interest not only in studying physics, but also in practicing dancing. Our focus was to understand how pirouette could help them understand elements of the rotation movement: angular and tangential velocities, moment of inertia and angular momentum. The educational product that guided the study and analysis was called “Pirouette and understand a little physics”, it contains a teaching sequence with five lessons, divided into experimental practical and observational activities, and the use of the software Tracker to analyze videos. It comprises a unit plan and lesson plans, instruction forms, questionnaires and registers (OQR), a handbook showing the assembling of experiments and materials used, videos produced by this author and other videos. The activities were devised based on Bruner’s approach, taking into account students’ autonomy in the learning process. According to the results, we identified Bruner’s approach in several moments such as the spiral curriculum and the discovery method, and many times we saw evidence of active and symbolic representations, effective potency and economy by means of observations and discussions as well as the OQR forms. Therefore, we observed that the teaching sequence based on Bruner’ approach that was proposed and presented in the educational product was a great helper and provoked students’ interest. It also helped students to understand elements of the rotational movement reaching the concept of angular momentum and its conservation.
Keywords: abordagem de Bruner; velocidade angular; momento de inércia; momento angular; pirueta; Bruner’s approach; angular velocity; moment of inertia; angular momentum; pirouette